Comparative clinical study of Apamarga Kshara application, infrared coagulation and Arshohara Vati in the management of Arsha (1(st) and 2(nd) degree hemorrhoids) - Sudarmi, Komang (Ayu, 2017)
INTRODUCTION: In anorectal disorders, incidences of piles and fissures are increasing in Indian population due to western lifestyle. Many surgical methods are available to cure anorectal disorders, but now a days, demand for Ayurveda and herbal preparation is increasing in society. MATERIALS AND METHODS: In this study, Apamarga Kshara application, infrared coagulation (IRC) procedure and Arshohara Vati (AV) tablet were administered for the management of internal hemorrhoid (Arsha). This study was an open labelled, prospective, interventional study, in which patients of piles [n = 30 (10 each group)] were selected from OPD of Institutional hospital. Apamarga Kshara application (AKA) was done on the internal piles for 1–3 sittings as per requirement, IRC was applied at the base of piles for one sitting and two tablets (500 mg each tablet) of AV were given orally thrice a day for 15 days. In all the three groups, the patients were assessed every week for 1 month and were followed up for another 1 month for relief in signs and symptoms. RESULTS: Obtained results were analyzed and encouraging results were observed after completion of the treatment. CONCLUSION: The study concluded that Apamarga Kshara application is the most effective treatment for the management of internal hemorrhoid of 1(st) and 2(nd) degree in comparison to IRC procedure and administration of Arshohara Vati.